Analisis Pola Konsumsi di Indonesia sebagai Indikator Peningkatan Kesejahteraan Masyarakat - Ayunda Febri Kinanti; Muhammad Syahrul Maulana; Muhammad Yasin (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Household consumption expenditure is a key indicator that can describe the welfare of households in a region or country. Household welfare as measured by consumption is related to how the household meets its basic needs, both food and non-food. The higher the proportion of consumption expenditure for non-food, the better the standard of living or household welfare because theoretically food consumption has a maximum limit, while non-food consumption has no maximum limit (BPS, 2020).